An evaluation model for the dissemination of earthquake emergency information and decision-making based on user demand - Zhang, Yi; Zhou, Yan; Zhou, Qi; Zheng, Yi; Tang, Shuya; Yan, Jinxu (Frontiers in Earth Science, 2025)
IntroductionTo reduce the risks associated with earthquake relief decision-making and improve the efficiency of earthquake information services, this paper proposes a seismic emergency decision-making utility evaluation process and emergency information utility evaluation method based on the perception of user demand, starting from user needs.Materials and MethodsAn evaluation model is constructed based on user preferences, information volume, and decision effectiveness. This article explores the quantification of earthquake emergency information utility and the decision-making utility evaluation process. It establishes a user preference model using Bayesian methods, introduces information entropy into it, and constructs a quadratic polynomial function linking demand probability, information quantity, and utility to quantify the decision-making utility of information products. Based on the threshold, effective information products were selected.ResultsThe reliability was tested, and the results showed that the correlation coefficient (R2), root mean square error (RMSE), and bias of the modeling set were 0.8955, 0.6492, and 0.0033, respectively. In addition, a 5-fold cross-validation was conducted to confirm the model's robustness and stability across different data partitions. The 6.0-magnitude earthquake that occurred in Luxian County, Sichuan Province, in 2021 was used as an example to test the feasibility of the evaluation process, demonstrating the rationality and effectiveness of the model.ConclusionThis method provides a new approach for evaluating information utility in a set scenario, which is beneficial for improving the decision-making ability of earthquake resistance and disaster-relief management, and effectively reducing the losses caused by earthquakes.